Bipotency of thymic epithelial progenitors comes in sequence. Issue 3 (11th March 2013) - Peterson, Pärt; Laan, Martti
<x xml:space="preserve">Abstract</x> In the thymus, in order to become MHC‐restricted self‐tolerant T cells, developing thymocytes need to interact with cortical and medullary thymic epithelial cells (TECs). Although the presence of a common bipotent progenitor for these functionally and structurally distinct epithelial subsets has been clearly established, the initial developmental stages of these bipotent cells have not been well characterized. In this issue of the European Journal of Immunology, Baik et al. [Eur. J. Immunol. 2013.43: 589–594] focus on the phenotypical changes of the early bipotent populations and show how the cortical and medullary markers are sequentially acquired during TEC development. These findings argue against a binary model in which both cortical and medullary lineages diverge simultaneously from lineage‐negative TEC progenitors and highlight an unexpected overlap in the phenotypic properties of these bipotent TECs with their lineage‐restricted counterparts.